Association of Interleukin-2-330T/G and Interleukin-10-1082A/G Genetic Polymorphisms with B-Cell Non-Hodgkin Lymphoma in a Cohort of Egyptians - Hala Aly Abdel Rahman; Mervat Mamdooh Khorshied; Ola Mohamed Reda Khorshid; Heba Mahmoud Mourad (Turkish Journal of Hematology, 2018)
Objective: Polymorphisms in the interleukin (IL)-2 and IL-10 genes are known to be associated with susceptibility to different immunedysregulated disorders and cancers such as non-Hodgkin lymphoma (NHL). To explore the possible association between IL-2-330T/G and IL- 10-1082A/G single-nucleotide polymorphisms and the susceptibility to B-cell NHL (B-NHL) in Egyptians, we conducted a case-control study. Materials and Methods: Genotyping of the studied genetic variations was done for 100 B-NHL patients as well as 100 age- and sex-matched healthy controls. Results: The IL-2 variant allele occurred at a significantly higher rate in patients than controls and was associated with susceptibility to B-NHL [odds ratio (OR): 1.91, 95% confidence interval (CI): 1.28-2.85]. It was also associated with advanced performance status score. IL-2 polymorphism conferred an almost threefold increased risk of diffuse large B-cell lymphoma (OR: 2.64, 95% CI: 1.35-5.15) and a fourfold increased risk of indolent subtypes (OR: 4.34, 95% CI: 1.20-15.7). The distribution of IL-10-1082A/G genotypes in our patients was close to that of the controls. Co-inheritance of the variant genotypes of IL-2 and the common genotype of IL-10 conferred an almost sixfold increased risk (OR: 5.75, 95% CI: 1.39-23.72), while co-inheritance of the variant genotypes of IL-2 and IL-10 conferred fivefold increased risk of B-NHL (OR: 5.43, 95% CI: 1.44-20.45). The variant genotypes of IL-2-330T/G and IL-10-1082A/G had no effect on the disease-free survival of B-NHL patients. Conclusion: The present study highlights the possible involvement of the IL-2-330T/G genetic polymorphism in the susceptibility to B-NHL in Egypt, especially indolent subtypes. Moreover, IL-10-1082A/G is not a molecular susceptibility marker for B-NHL in Egyptians.